ANALISIS DAMPAK KERUSAKAN INFRASTRUKTUR AKIBAT LIKUIFAKSI DI PALU - Sainuddin Sainuddin (Universitas Tamansiswa Padang, 2022)
The objectives of this study was to (1) analyze infrastructure damages (buildings and roads) due to liquefaction based on Open Street Map (OSM) data, (2) analyze spatial distribution patterns of infrastructure damage due to liquefaction, (3) analyze the characteristics of satellite imagery before and after liquefaction based on the time series (sentinel 2) satellite image index. The results showed that the Petobo was the most affected by liquefaction, with a percentage of damage in roads is 83.7% and buildings is 99.68%. Then the results was obtained from the spatial spread analysis of pattern have been analyzed and mapped with the heatmap method and the 100mmx100m grid method. The tendency of the distribution pattern of buildings (Petobo, Balaroa, and Jono Oge) follows the standard distance ellips method, while the distribution of buildings (Lolu) follows the standard distance pattern. Furthermore, the results of the spatial analysis of NDVI satellite images show the colors shading that indicate vegetation or the level of density (greening) on a land where the green color indicates the density on a land. While the results of the spatial analysis of NDWI images explain the distribution of colors that show humidity in a land.